2020
DOI: 10.1038/s41598-020-78649-9
|View full text |Cite
|
Sign up to set email alerts
|

Cascade synthesis and optoelectronic applications of intermediate bandgap Cu3VSe4 nanosheets

Abstract: Two-dimensional (2D) ternary materials recently generated interest in optoelectronics and energy-related applications, alongside their binary counterparts. To date, only a few naturally occurring layered 2D ternary materials have been explored. The plethora of benefits owed to reduced dimensionality prompted exploration of expanding non-layered ternary chalcogenides into the 2D realm. This work presents a templating method that uses 2D transition metal dichalcogenides as initiators to be converted into the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…This study also showed that increasing the excitation wavelength caused a redshift in the peak position, which was attributed to the distribution of both size and different emissive sites of the nanocrystals. The same group also investigated Cu 3 VSe 4 in nanosheet form with comparable results regarding the photoluminescence and absorption bands [8].…”
Section: Optical Propertiesmentioning
confidence: 87%
See 4 more Smart Citations
“…This study also showed that increasing the excitation wavelength caused a redshift in the peak position, which was attributed to the distribution of both size and different emissive sites of the nanocrystals. The same group also investigated Cu 3 VSe 4 in nanosheet form with comparable results regarding the photoluminescence and absorption bands [8].…”
Section: Optical Propertiesmentioning
confidence: 87%
“…However, the synthesized product did not have good crystallinity, and a post-annealing process was utilized to improve the crystallinity of the Cu 3 VS 4 nanoparticles. Later, the syntheses of cubic Cu 3 VS 4 nanocubes [12], Cu 3 VSe 4 nanocubes [9], and Cu 3 VSe 4 nanosheets [8] were reported. Extending the reaction time leads to the facile preparation of high purity Cu 3 VS 4 and Cu 3 VSe 4 without the postannealing treatment.…”
Section: Solution-phase Synthesismentioning
confidence: 99%
See 3 more Smart Citations